Bumblebees, the proficient mountain pollinators: evidence from Stachys germanica (Lamiaceae) along the altitudinal gradient of Mount Olympus, Greece. (23rd August 2021) - Minachilis, Konstantinos; Kantsa, Aphrodite; Petanidou, Theodora
Abstract: Pollen limitation and its drivers along altitudinal clines form a controversial topic, highlighting the need for more studies and in different biomes. We tested the hypothesis that the populations of a predominantly bee-pollinated plant are pollen-limited along elevations and examined whether this is related to bee visitation rate. For two years, we studied flower visitation, pollen limitation and mating system using five populations of Stachys germanica L. occurring between 327 and 1936 m a.s.l. on Mt. Olympus, Greece. S. germanica showed moderate to high self-compatibility, low spontaneous self-pollination and low pollen limitation across all altitudes and years. Bumblebees were the dominant pollinators; their visitation increased with altitude and was positively correlated with seed set and negatively correlated with pollen limitation. The opposite trend was found for the visitation by other pollinators. Seed mass was independent of visitation. Low pollen limitation is evidently due to high bumblebee visitation along the altitude, whereas seed mass could be linked to resource availability or environmental conditions. Our findings underline the functional role of bumblebees on Mediterranean mountains, and the need to focus on bumblebee conservation on this legendary mountain.